Metodologias ativas no ensino médio concomitante com o ensino profissional e utilização de tecnologias digitais da informação e comunicação - Carvalho, Waldemar José Baptista de (2018)
The present work aims at narrating a teaching experience in the Math discipline of the second year of a Technical High School (ETEC) in São Paulo, Brazil, approaching the subject Matrices, Determinants and Systems, and to interrelate that experience with the practices of Active Methodologies, using Digital Information and Communications Technologies (DICT) identified in the literature. It also aims at conducting a survey of PhD theses, Mastering dissertations and papers available in the database of the Coordination of Personal Improvement of Higher Education (CAPES) on the practices of Active Methodologies in High School, concomitantly with the Professional Technical Education, with the use of DICT, in the framework of a literature review. We seek to meet these objectives from a literature review based on Vygotsky’s social interactionist frameworks, Ausubel’s meaningful learning and Papert’s constructionism, rewritten in the contemporaneousness of Almeida and Valente, as well as by designing, applying and analyzing a project conducted with math students of a Technical High School for verifying whether the application of a ‘hybrid methodology’ in that context would bring positive or negative results, or even if it would not entail any change in that framework. In our survey on the CAPES database, we searched for studies that mentioned experiences of teachers who applied the active methodologies with the use of DICT and that provided students with active learning. We found forty-eight studies, seven of which aimed to describe research related to High School. The results were tabulated and presented in four tables. The conclusions in the analyzed studies show a good rate of student achievement; teachers' satisfaction in applying the active methodologies with DICT; changes in teachers’ practice; and low number of reports on the use of DICT in the High School teaching and learning processes. Regarding the experience conducted in this study, the results show that was extremely valuable for all parties involved and that it occurred a hybridization process with the application of the traditional teaching methodology together with the active methodologies, with the use of DICT, providing all the research participants a differentiated course dynamic if compared to those previously lived. Our study concludes by pointing out that changes in the educational contexts of Brazilian Technical Education of level medium are feasible as well as that they should be implemented for fostering a learning process that better meets the contemporary students’ needs, but, nevertheless, that this process should take place considering the characteristics of the environment and the context of application